2020
DOI: 10.9734/ejmp/2020/v31i230210
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Silver Nanoparticle by Using Cassia auriculata Extract

Abstract: In this study, green synthesis of silver nanoparticles (Ag NPs) has done using traditional herbal namely Cassia auriculata extract by the simple Green synthesis method. The synthesized Ag nanoparticles were studied by the characterization techniques includes X-ray diffraction (XRD) crystallography for nature of crystalline with relevant parameters, Transmission electron microscopy (TEM) for particle size as well as the SAED patterns for amorphous, crystalline or polynanocrystalline and Photoluminescence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a recent study, Nawaz et al reported the anti-breast cancer effect of the ethanolic extract of C. auriculate on MCF-7 cell lines, with half maximal inhibitory concentration (IC 50 ) values of about 84.56 µg/mL, in an in vitro cytotoxicity assay. They further reported that the use of AgNPs obtained via green synthesis enhanced the cytotoxic potential of the extract by reducing the IC 50 to 17.25 µg/mL [17]. In another study, the ethanolic extracts of C. auriculata leaves were found to inhibit only~47% of MCF-7 and Hep-2 cells at higher concentrations of 400µg/mL and 500µg/mL, respectively [18].…”
Section: Introductionmentioning
confidence: 94%
“…In a recent study, Nawaz et al reported the anti-breast cancer effect of the ethanolic extract of C. auriculate on MCF-7 cell lines, with half maximal inhibitory concentration (IC 50 ) values of about 84.56 µg/mL, in an in vitro cytotoxicity assay. They further reported that the use of AgNPs obtained via green synthesis enhanced the cytotoxic potential of the extract by reducing the IC 50 to 17.25 µg/mL [17]. In another study, the ethanolic extracts of C. auriculata leaves were found to inhibit only~47% of MCF-7 and Hep-2 cells at higher concentrations of 400µg/mL and 500µg/mL, respectively [18].…”
Section: Introductionmentioning
confidence: 94%
“…This activity, however, could be the outcome of a dynamic relationship between biologically active phytoconstituents adhering to the surfaces of the particles and the nanosized silver. The more significant cytotoxicity of AgNPs might also be related to their size and the capping of biomaterials on the surfaces of nanoparticles, like protein or phenol [90]. The mode of action may involve an increase in neoplastic transformation followed by apoptosis, dose-dependent apoptosis-inducing abilities, necrosis of cancer cell lines, or other mechanisms involving epigenetic and signal transduction pathways [91].…”
Section: Cytotoxic Activitymentioning
confidence: 99%